Functionalization Mesoporous Silica using Aminopropyltriethoxysilane (APTES) as Adsorbent for Removal Ni (II) from Aqueous Solution - Ega Hidayani; Andriayani Andriayani; Muhammad Taufik (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
This study successfully synthesized mesoporous silica using the template methyl ester ricinoleate (MS-TMR) and further functionalized the MS-TMR surface with 3-aminopropyltriethoxysilane (APTES). The functionalization of MS-TMR with APTES was achieved through a 48-hour grafting method. For the adsorption experiments, 20 mg of both MS-TMR and MS-TMR-APTES adsorbents were employed to remove Ni(II) from aqueous solutions at a concentration of 30 mg/L and pH 6. The objective was to assess the adsorption capacity and to characterize the synthesized adsorbents. Characterization was conducted using Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). FTIR analysis revealed that the MS-TMR adsorbent possessed silanol (Si-OH) and siloxane (Si-O-Si) groups. Conversely, the MS-TMR-APTES adsorbent exhibited additional amine (N-H) and C-H groups after the APTES grafting. XRD results indicated that both samples were amorphous. The concentration of Ni(II) ions was determined using Atomic Absorption Spectroscopy (AAS), which facilitated the calculation of removal percentages and adsorption capacities. MS-TMR achieved a mere 3.54% removal of Ni(II) ions, corresponding to an adsorption capacity of 3.21 mg/g. In contrast, MS-TMR-APTES demonstrated significantly enhanced performance, removing 54.23% of Ni(II) ions with an adsorption capacity of 48.81 mg/g. The findings suggest that APTES-functionalized MS-TMR has considerable potential for removing Ni(II) ions and could be explored further for the adsorption of other heavy metal ions.